Seeds in farmers' hands: community seed banking in China - Guanqi Li; Vernooy, Ronnie; Song, Yiching (Sino-German Agricultural Centre (DCZ), 2022)
Topics in this article include: What is a community seedbank and why it matters / the Chinese way of community seedbanking / three examples of community seed banks in China / challenges, prospects and the way forward